Improving the Digital Literacy Skills of Junior High School Students through Blended Learning - Andika, Andi Nurul Adha; Adnan, Adnan; Jamaluddin, Asham Bin (Jurnal Pendidikan MIPA, 2025)
This study aims to determine the effect of various blended learning models on digital literacy, namely station rotation, lab rotation, and pedati. This study is a true experimental study using a pretest-posttest control group design. The research population included all eighth grade students at SMP Negeri 2 Sengkang. The research sample was taken using random sampling, resulting in four classes, namely VIII.1 as the control class with STAD learning, and three experimental classes: VIII.2 with blended learning station rotation, VIII.3 with blended learning lab rotation, and VIII.4 with blended learning pedati. The instrument used was the students' digital literacy instrument. Data was collected through a digital literacy questionnaire that was given before and after learning. Data analysis was performed using ANCOVA with a significance level of 0.05. The results revealed that the application of blended learning with the station rotation, lab rotation, and pedati models influenced digital literacy. Based on the LSD (Least Significant Difference) follow-up test, blended learning with the lab rotation model obtained the highest average score compared to the other two models. This finding emphasizes the importance of technology integration in the learning process, especially in improving students' digital literacy.    Keywords: digital literacy, station rotation, lab rotation, pedati.